Chiral 3D‐printed Bioelectrodes. (16th February 2021) - Muñoz, Jose; Redondo, Edurne; Pumera, Martin
Abstract: 3D printing technology has gained great interest since it enables decentralized and customized manufacturing of 3D‐printed electronic devices. From an electrochemical point of view, 3D‐printed electrodes present promising achievements for (bio)sensing approaches. Herein, the feasibility of exploiting 3D‐printed electrode substrates toward chiral analyses—a relevant topic owing to the homochiral nature of the biochemistry of life—has been interrogated for the first time. As a proof‐of‐concept, as‐printed 3D‐printed nanocomposite carbon electrodes (3D‐nCEs) have been biofunctionalized with a model chiral selector like the class‐enzyme L‐amino acid oxidase for the ultrasensitive electrochemical discrimination of amino acid enantiomers. Interestingly, an unprecedented electrochemical approach has been devised, which relies on impedimetrically monitoring changes at the bioelectrode interface derived from the reactivity between the H2 O2 by‐product generated during enzymatic reactions and the 3D‐nCE surface, yielding to the screening of amino acid enantiomers even at femtomolar concentrations. Different characterization techniques have been employed to elucidate the impedimetric mechanism involved for the electroanalysis. Accordingly, this work not only demonstrates the feasibility of exploiting 3D‐printed electronic devices for enantiosensing achievements, but also brings out a general and straightforward electrochemical approach for the sensitive and selective analysis of enzymatic systems. Abstract : A chiral 3D‐printed biorecognition system is reported for the first time for the highly sensitive and selective discrimination of amino acid enantiomers by devising an unconventional impedimetric approach.